Role of surface microstructure of Mo back contact on alkali atom diffusion and Ga grading in Cu(In, Ga)Se2 thin film solar cells. Issue 3 (5th April 2019) - Gong, Junbo; Kong, Yifan; Li, Jianmin; Wang, Xiangqi; Que, Yande; Zhang, Zengming; Ding, Zejun; Xiao, Xudong
Abstract: While the major function of molybdenum (Mo) back contact on soda‐lime glass (SLG) substrate in Cu(In, Ga)Se2 (CIGS) solar cells is to provide good adhesion and good conductivity, its role as the transportation channel for alkali elements from SLG substrate to CIGS layer has often been overlooked. In this work, we have intentionally fabricated tri‐layered structure in contrast to the conventional bi‐layered structure for Mo back contact with the microstructure of the thin topmost Mo layer manipulated by the Ar pressure and water vapor during sputtering deposition. It has been discovered that the CIGS solar cell conversion efficiency can be greatly affected by this thin topmost Mo layer of the back contact. Investigations on the elemental depth profiles in the CIGS devices and the chemical states of Mo on the back contact surfaces have revealed that the surface layer of Mo back contact has a strong effect on the diffusion of alkali elements from SLG into CIGS absorber layer, which in turn influences the formation of Ga gradient in the CIGS layer and thus the solar cell performance. It was revealed that Mo(OH)6 and MoO3 formed on the surface of Mo back contact play a key role in determining the K atom distribution and Ga gradient. A reaction mechanism was also proposed. Abstract : The influence mechanism of Mo surface on alkali diffusion and Ga grading in CIGS was revealed. Our study has provided a simple method to control the alkali diffusion and Ga gradient in CIGS absorber. The revelation of the mechanism of alkali diffusion occurs on Mo surface is not only significant to CIGS study but also valuable for all kesterite‐based solar cells